Osamdeseta obljetnica Hrvatskoga sokola u Antofagasti - Mataić, Dane (2008)
The champions of Chile, South America and representatives who appeared at world championships and Olympic games were born on the sports fields of the Hrvatski sokol (Croatian Falcon) in Antofagasta. National pride and athletic elan kept morale high, and filled the trophy cases and newspapers with successes and the hearts of Croatians with joy and gratitude to their new homeland – Chile. Hrvatski sokol, founded by Ivan Goić Kuščević, has been a favourite gathering place for the full eighty years of Croatian emigration in Antofagasta, in which there are some 25,000 Croatian descendants living according to official statistics, most of which speak Spanish. The Hrvatski sokol sporting association was founded by Croatians and their descendants on 1 December 1927 at the hall of the then Yugoslav fire-fighter's brigade no.
Summary ; resumen
Keywords: Hrvati -- Sport; Čile